Service Factors to Increase Loyalty and Number of Priority Customers (Case Study of PT. Bank Sumut Syariah Binjai Sub-Branch) - Helva Diansyah Putri; Wahyu Syarvina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
In banking that runs a business in the service sector, service is the most important thing so that people are interested in becoming their customers. Currently, almost all banks in Indonesia have issued priority savings products, and to increase priority customers, banks are competing to provide the best service to attract customers. This study uses qualitative methods to collect data in the form of descriptive data in written and spoken language from people and observed behavior. The results of this study are the services and benefits provided to priority customers affect the increase in the number of customers and also the loyalty of priority customers at Bank Sumut Syariah Binjai Sub-Branch.